CapturePhos – A phosphorus-rich polymer as a homogeneous catalyst scavenger. Issue 13 (1st June 2017) - Cuthbert, T. J.; Evoy, E.; Bow, J. P. J.; Guterman, R.; Stubbs, J. M.; Gillies, E. R.; Ragogna, P. J.; Blacquiere, J. M.
Abstract : Homogeneous catalysts are efficiently removed from solution by an insoluble phosphorus-rich polymer network. Abstract : A soft polymer network prepared through a phosphane–ene reaction successfully sequestered Rh and Ru from hydrogenation and ring closing metathesis reactions, respectively. Scavenging effectively quenches catalytic activity and ultimately removes >98% of the metal.